Analisis Pengelolaan Persediaan Dengan Metode Economic Order Quantity (EOQ) Pada Toko Bunga Mart - Made Arista Amelia (PT. Hasba Edukasi Mandiri, 2025)
Inventory problems such as out of stock and overstock are significant challenges for many companies, including Bunga Mart. Using traditional calculation methods, Bunga Mart often experiences difficulties in determining the number of items that must be purchased, causing frequent shortages or excess stock. This research aims to analyze inventory control at Bunga Mart using the EOQ (Economic Order Quantity) method. The results show that implementing EOQ is effective in reducing inventory costs in 2023. Inventory costs for In Mild Cigarettes decreased from IDR 2,108,929 to IDR 1,790,245, Red Marlboro Cigarettes from IDR 437,942 to IDR 411,852, and White Marlboro Cigarettes from IDR 333,129 to IDR 320 ,449. The application of the EOQ method has been proven to increase the efficiency and effectiveness of inventory management and save operational costs.